From Existential Crisis to Flourishing: The Four Noble Truths as an Integrative Framework for Psychological Resilience in Wartime Ukraine - Lazorko, Olha (Psychological Prospects Journal, 2025)
Purpose. The article presents a conceptual and analytical study that explores the potential of adapting the Buddhist model of the Four Noble Truths as an integrative framework for psychological resilience in the context of the war in Ukraine. Traditionally serving as a guide for spiritual transformation, this philosophical approach is reinterpreted in this study as a secular framework for addressing existential crises, trauma, and loss. The model of the Four Noble Truths emerges as a metamodel that can integrate cognitive, emotional, ethical, behavioural, and spiritual components essential for working with clients experiencing profound psychological distress. The study aims to develop an interdisciplinary and holistic model that incorporates principles from existential psychology, positive psychology, trauma therapy, mindfulness-based approaches, and meaning-oriented practices. Methods. The methodology includes theoretical modelling, hermeneutic analysis of philosophical sources, comparative analysis of psychological theories, and descriptive elements drawn from clinical work with internally displaced persons, veterans, and clients diagnosed with PTSD. Results. The findings indicate that the Four Noble Truths model can serve as an effective metaphorical and structural tool for psychological support. It facilitates the processing of pain, helps identify the sources of mental suffering, activates internal resources, and aids in the transition from trauma to inner maturity, meaning-making, and flourishing. Special attention is given to compassion, ethical engagement, narrative reconstruction, and existential reflection as key inner renewal and integrative healing components. Conclusions. In conclusion, the proposed framework’s practical significance is highlighted in psychological counselling, group therapy, crisis intervention, and psycho-emotional recovery programs aimed at civilians, military personnel, and volunteers. The model also shows potential for integration into educational curricula, digital learning platforms, resilience training programs, and interdisciplinary psychotherapeutic practices in conditions marked by deep social, moral, and existential instability.